2017
DOI: 10.1007/s12253-017-0191-9
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Interleukin 1 Polymorphism and Helicobacter pylori Infection: an Increased Risk of Gastric Cancer in Pakistani Population

Abstract: Helicobacter pylori is one of the major risk factors involved in the development ofgastritis and gastric cancer (GC). H. pylori infection leads to increased production of pro-inflammatory cytokines by the host. Carriage of specific polymorphisms in cytokine genes may be associated with host susceptibility to the development of GC. We investigated the role of host genetic factors including polymorphisms of IL-1B and IL-1RN in correlation with gastritis and GC in H. pylori infected Pakistani population. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…H pylori can stimulate the production of a variety of cytokines. 29 H pylori can induce the secretion of IL-1β, 30,31 resulting in an increase in IL-1β levels. [32][33][34] The increase in IL-1β level is closely correlated to the occurrence and development of H pylori infection-associated gastritis.…”
Section: Discussionmentioning
confidence: 99%
“…H pylori can stimulate the production of a variety of cytokines. 29 H pylori can induce the secretion of IL-1β, 30,31 resulting in an increase in IL-1β levels. [32][33][34] The increase in IL-1β level is closely correlated to the occurrence and development of H pylori infection-associated gastritis.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, intrinsic mutations and polymorphisms in IL-1 genes have been implicated as well in many cancer types as reviewed by Khazim et al [79], though results from studies are sometimes conflicting, and the association is not always clear. Single and IL-1 gene-cluster polymorphisms have been suggested to be associated with cancers such as cervical [80] and ovarian cancer [81], MM [82], esophageal [83], colorectal cancer (CRC) [84], NSCLC [85], pancreatic cancer [86], prostate cancer [87], and gastric cancer [88][89][90].…”
Section: Il-1 Dysregulation and Its Contribution To Cancer And Tumorimentioning
confidence: 99%
“…Interleukin (IL-1) gene complex consists of IL-1α, IL-1β, IL-1R, and IL-RA genes with five potent polymorphic loci in the structural and promoter regions [40]. These polymorphic loci are associated with susceptibility for sepsis in trauma patients of the Chinese population [41,42] and also associated with other diseases, such as cancer and autoimmunity [43,44]. In our study, we have reported the changes in alleles and genotype frequency at the promoter region of IL-1β (À511) gene.…”
Section: Role Of Cytokine Gene Polymorphism In Sepsismentioning
confidence: 99%